Assimilate Partition of Potato (Solanum tuberosum L.) as Response to Combination of Paclobutrazol and Nitrogen - Semuel Runtunuwu; Edy F. Lengkong; Stella Tulung; Deisire N.S. Darus; Riung Tumambo (Jurnal Ilmiah Sains, 2024)
Increasing the productivity of potato (Solanum tuberosum L.) can be done by increasing biological production (biomass) and the ability to convert (partition) assimilate/photosynthate into economic results (tubers). The aim of this research is to find a better combination of paclobutrazol (PBZ) application and nitrogen (N) fertilization for tuber partition assimilate of potato. The experiment was conducted in Randomized Block Design (RBD) with three replications. The treatment was consists of  nine combinations of PBZ treatments and N  fertilization as follows: 1) 3 kg PBZ/ha + 200 kg N/ha, 2) 3 kg PBZ/ha + 250 kg N/ha, 3) 3 kg PBZ/ha + 300 kg N/ha, 4) 3,5 kg PBZ/ ha + 200 kg N/ha, 5) 3,5 kg PBZ/ha + 250 kg N/ha, 6) 3,5 kg PBZ/ha + 300 kg N/ha, 7) 4 kg PBZ/ha + 200 kg N/ha, 8) 4 kg PBZ/ha + 250 kg N/ha, 9) 4 kg PBZ/ha + 300 kg N/ha. The research results showed that at the beginning of growth up to 42 DAP (day after plan), the assimilate (dry material) was directed towards stem and leaf (shoot) growth. Next, at 56 DAP to 84 DAP the assimilate is allocated for tuber growth. The combination of 4 kg PBZ/ha + 200 kg N/ha produces the largest tuber weight Keywords: Potato (Solanum tuberosum L);  nitrogen; paclobutrazol; partition assimilate